Measures of External Competitiveness for Germany - Feldman, Robert (Washington, D.C. : International Monetary Fund, 1994)
This paper assesses Germany's external competitive position from several angles. It first examines movements in several real exchange rate indices. The analysis of competitiveness is then supplemented by using the so-called constant market share approach, and finally by examining briefly both pressures on profit margins in the tradable goods sector as well as export prospects. A key conclusion of the analysis is that the deterioration of Germany's external competitiveness suggested by some commonly used indicators of the real appreciation of the deutsche mark, such as those based on relative unit labor costs in manufacturing, is generally exaggerated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet